2021
DOI: 10.1097/ccm.0000000000005283
|View full text |Cite
|
Sign up to set email alerts
|

Barotrauma in Coronavirus Disease 2019 Patients Undergoing Invasive Mechanical Ventilation: A Systematic Literature Review*

Abstract: There are concerns of a high barotrauma rate in coronavirus disease 2019 patients with acute respiratory distress syndrome receiving invasive mechanical ventilation. However, a few studies were published, and reported rates were highly variable. We performed a systematic literature review to identify rates of barotrauma, pneumothorax, and pneumomediastinum in coronavirus disease 2019 acute respiratory distress syndrome patients receiving invasive mechanical ventilation.DATA SOURCE: PubMed and Scopus were searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
58
4
22

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(94 citation statements)
references
References 47 publications
3
58
4
22
Order By: Relevance
“…Most of previously published studies reported no significant differences among mechanical ventilation settings/parameters between patients who developed barotrauma and those who did not. They also found a trend towards lower age and higher use of steroids in pneumothorax patients, which were also suggested by other Authors [2,16].…”
supporting
confidence: 83%
See 3 more Smart Citations
“…Most of previously published studies reported no significant differences among mechanical ventilation settings/parameters between patients who developed barotrauma and those who did not. They also found a trend towards lower age and higher use of steroids in pneumothorax patients, which were also suggested by other Authors [2,16].…”
supporting
confidence: 83%
“…They found that pneumothorax rate among invasively ventilated COVID-19 patients is 80/594 (13 %), and mortality rate for patients who developed pneumothorax is 50/80 (62 %). On the contrary, among 160 randomly selected invasively ventilated COVID-19 patients without pneumothorax, mortality was 78/ 160 (49 %).We recently published a systematic review on rate of barotrauma among invasively ventilated COVID-19 patients [2]. Our pooled analysis included data from 13 studies and 1814 patients [3][4][5][6][7][8][9][10][11][12][13][14][15] and we found that pooled estimate of pneumothorax rate was 10.7 % (95 % confidence interval [CI] = 6.7 %-14.7 %), while overall rate of barotrauma event was 16.1 % (95 % CI = 11.8 %-20.4 %).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A possible explanation could lie in the previously proposed virus-induced lung frailty, which is thought to be a main contributor for the high incidence of barotrauma in COVID-19 patients. 67,68 In this prospective, the honeycombing CT pattern, when present, could represent a subpleural cluster of small pneumatoceles rather than cystic air spaces resulting from irreversible lobular disruption.…”
Section: Implications Of Study Findingsmentioning
confidence: 70%